UPAYA GURU BK DALAM MENGEMBANGKAN SIKAP POSITIF PESERTA DIDIK TERHADAP LAYANAN KONSELING - Hananto, Ipung (Universitas Borneo Tarakan, 2022)
Guidance and counseling are support services offered to students to help them become independent and develop to their full potential. Students' potential is anticipated to grow in a variety of areas, including social and personal life, learning ability, and mature career preparation. The school counselor's counseling services should be able to be utilized to identify and assist in resolving issues that pupils need to work through with the school counselor. The goal of this study was to evaluate the efforts made by BK teachers to change their students' perceptions of counseling services. This research's methodology is a case study-based descriptive qualitative analysis. Moreover, interviews and documentation were utilized as data gathering methods, and data reduction, presentation of the data, and conclusion drawing were employed as data analysis methods. The results obtained from this study are that so far the services that have been carried out have not been optimal so that the efforts of the school counselor are needed to improve in terms of their services professionally, improve skills in self-approaching students, be proactive in conducting counseling services, establish collaboration with homeroom teachers and teachers subjects in developing students' positive attitudes, distributing questionnaires related to students' positive attitudes towards counseling services to analyze and interpret the data, form peer counseling as an effort to help solve peer problems, and provide facilities and infrastructure as well as adequate facilities and rooms.Keywords : positive attitude, counseling services